2019
DOI: 10.15403/jgld-263
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Contrast-Enhanced Ultrasonography for Real Time Monitoring of Laparoscopic Radiofrequency Ablation for Hepatocellular Carcinoma: an Observational Pilot Study

Abstract: Background and Aims: Laparoscopic radio-frequency ablation (L-RFA) for hepatocellular carcinoma (HCC) is used for unresectable tumors, with difficult location, unfitted for a percutaneous ablation technique. L-RFA has a high incidence of local recurrence. Even if intraoperative-ultrasound is standardized for staging and RFA probe guidance, the role of laparoscopic contrast-enhanced ultrasound (L-CEUS) for the real time monitoring of L-RFA efficacy has not been previously reported. We evaluated in a pilot obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Compared to percutaneous and no CEUS groups, we can see longer PFS in the laparoscopic group, intraoperative CEUS group, and laparoscopic CEUS group, especially in the laparoscopic CEUS group, though there is no statistical difference. Bartoș et al demonstrated that local recurrence was lower in the laparoscopic group than in the percutaneous group in the study of ablation of liver metastases, which was consistent with our views 14 . However, RFA is only a part of the comprehensive treatment of CRLM, which is not a local disease but a systemic disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared to percutaneous and no CEUS groups, we can see longer PFS in the laparoscopic group, intraoperative CEUS group, and laparoscopic CEUS group, especially in the laparoscopic CEUS group, though there is no statistical difference. Bartoș et al demonstrated that local recurrence was lower in the laparoscopic group than in the percutaneous group in the study of ablation of liver metastases, which was consistent with our views 14 . However, RFA is only a part of the comprehensive treatment of CRLM, which is not a local disease but a systemic disease.…”
Section: Discussionsupporting
confidence: 90%
“…Bartoș et al demonstrated that local recurrence was lower in the laparoscopic group than in the percutaneous group in the study of ablation of liver metastases, which was consistent with our views. 14 However, RFA is only a part of the comprehensive treatment of CRLM, which is not a local disease but a systemic disease. Although almost all the patients with liver metastases get to the status of no evidence of disease (NED) by RFA, local recurrence and 15 Therefore, the efficacy of RFA for laparoscopic HCC may be more meaningful, but it is a pity that there is no further analysis to form the cohort in our study due to the small number of HCC cases the in laparoscopic group.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of this maneuver is the reduction of the cooling effect induced by the proximity of tumors to main vascular branches (“heat sink”), the rate of achieving a complete ablation being higher[ 18 ]. Evaluation of the necrotic area and the efficacy of RFA can be performed immediately by contrast-enhanced-IOUS (CE-IOUS), making possible repeated ablation sessions immediately[ 19 ].…”
Section: Combined Treatment To Facilitate Curementioning
confidence: 99%
“…This technique, already used in open surgery [4], should be considered as complementary to the intraoperative ultrasound: it provides new findings that are based on the pattern of enhancement due to the tumor vascularity. Laparoscopic CEUS is also useful for an immediate evaluation after radiofrequency ablation and permits adjunctive ablations, reducing the risk of local recurrences [5].…”
mentioning
confidence: 99%